Strategi Pembelajaran Kecerdasan Spasial Pengolahan Visualisasi Dalam Memahami Mata Kuliah Nirmana 2 Dimensi (Dwimatra) - Yuda Nugraha Jamaludin (Jurusan Seni Rupa ISBI Bandung, 2025)
The Visual Communication Design study program has a 2-dimensional (two-dimensional) Nirmana course as an initial means for students to recognize the basics of visual forms. These elements or elements are explored using basic principles of visual form and design to produce a work that has high aesthetic value. The Nirmana course is one of the initial steps for students to train their sensitivity and develop their creativity. The purpose of this study is to discuss optimal learning strategies so that the objectives are achieved in accordance with the vision and mission of the 2-dimensional (twodimensional) Nirmana course listed in the curriculum. The method in this study applies the classroom action method with the PTK (Classroom Action Research) model approach from Kurt Lewin, which focuses on exploring the role of spatial intelligence teaching strategies on the process of developing student creativity in 2-dimensional (two-dimensional) Nirmana learning. Students in the fields of art and design are closely related to creativity and sensitivity, of course they need preparation in understanding the governance of design elements. Spatial intelligence, namely the ability to visualize ideas related to space and place. Modification of the 2-dimensional (two-dimensional) Nirmana learning strategy with contextual (visual-spatial) and assessment evaluation can be an important point in organizing a conducive classroom atmosphere, improving the quality of learning enthusiasm and improving students’ understanding and creativity to work. The analysis process is carried out through the collection of measurable data.